Online collaborative visual novel creator and player using HTML5 - Argulla, Greg Daniel Ongoco (Animo Repository, 2014)
The creation and development of a visual novel, like many other forms of game development, requires many different forms of collaboration and communication. However, in the case of visual novels, there is a distinct lack of such collaborative tools. Moreover, with the current practices in visual novel development there exists a problem regarding project compilation and asset availability. This paper describes a proposed solution to the lack of collaborative processes in the development of visual novels and the issues of compilation and asset availability. In order to address all the issues pertaining to the lack of collaborative features and asset availability, an online system, the Online Collaborative Visual Novel Creator (OCVNC) was developed. The OCVNC is an project adapting concepts from the previous work of Apostol et al, VAST Fire: A Non-linear Storyboarding Tool For Visual Novels. Similar to VAST Fire, the OCVNC caters to the needs of those with minimal to no programming knowledge or expertise as the tool allows users to create and storyboard a visual novel without any programming involved.